Composition and Interactions among Bacterial, Microeukaryotic, and T4-like Viral Assemblages in Lakes from Both Polar Zones - Daniel, Aguirre de Cárcer; Pedrós-Alió, Carlos; Pearce, David A.; Alcamí, Antonio (Frontiers in Microbiology, 2016)
In this study we assess global biogeography and correlation patterns among three components of microbial life: bacteria, microeukaryotes, and T4-like myoviruses. In addition to environmental and biogeographical considerations, we have focused our study on samples from high-latitude pristine lakes from both poles, since these simple island-like ecosystems represent ideal ecological models to probe the relationships among microbial components and with the environment. Bacterial assemblages were dominated by members of the same groups found to dominate freshwater ecosystems elsewhere, and microeukaryotic assemblages were dominated by photosynthetic microalgae. Despite inter-lake variations in community composition, the overall percentages of OTUs shared among sites was remarkable, indicating that many microeukaryotic, bacterial, and viral OTUs are globally-distributed. We observed an intriguing negative correlation between bacterial and microeukaryotic diversity values. Notably, our analyses show significant global correlations between bacterial and microeukaryotic community structures, and between the phylogenetic compositions of bacterial and T4-like virus assemblages. Overall, environmental filtering emerged as the main factor driving community structures.